2016
DOI: 10.1002/2015jg003240
|View full text |Cite
|
Sign up to set email alerts
|

Spring bloom dynamics in a subarctic fjord influenced by tidewater outlet glaciers (Godthåbsfjord, SW Greenland)

Abstract: In high-latitude fjord ecosystems, the spring bloom accounts for a major part of the annual primary production and thus provides a crucial energy supply to the marine food web. However, the environmental factors that control the timing and intensity of these spring blooms remain uncertain. In 2013, we studied the spring bloom dynamics in Godthåbsfjord, a large fjord system adjacent to the Greenland Ice Sheet. Our surveys revealed that the spring bloom did not initiate in the inner stratified part of the fjord … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(76 citation statements)
references
References 28 publications
1
75
0
Order By: Relevance
“…During summer, the upper stratification is maintained by runoff (estuarine circulation), subglacial freshwater discharge (subglacial circulation), and glacial ice melt. During winter the upper stratification is a result of sea ice cover and (dense) coastal inflow (Meire et al, ; Mortensen et al, ). Two circulation modes are associated with lifting of isotherms near the sea surface in the inner part of the fjord: dense coastal inflows during winter and subglacial circulation during summer, and both contribute to maintaining the 1 °C isotherm at ~20‐m depth for at least 8 years, that is, from 2008 to winter 2016.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…During summer, the upper stratification is maintained by runoff (estuarine circulation), subglacial freshwater discharge (subglacial circulation), and glacial ice melt. During winter the upper stratification is a result of sea ice cover and (dense) coastal inflow (Meire et al, ; Mortensen et al, ). Two circulation modes are associated with lifting of isotherms near the sea surface in the inner part of the fjord: dense coastal inflows during winter and subglacial circulation during summer, and both contribute to maintaining the 1 °C isotherm at ~20‐m depth for at least 8 years, that is, from 2008 to winter 2016.…”
Section: Resultsmentioning
confidence: 99%
“…During summer, the upper stratification is maintained by runoff (estuarine circulation), subglacial freshwater discharge (subglacial circulation), and glacial ice melt. During winter the upper stratification is a result of sea ice cover and (dense) coastal inflow (Meire et al, 2016;Mortensen et al, 2014). Two circulation modes are associated with lifting of…”
Section: Variability In the Outer And Inner Fjordmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, Hornsund with tidewater glaciers is particularly susceptible to the influence of glacier melting, which releases fresh meltwater and drifting ice to fjords. These processes have shown to supply modern and ancient OM, trace metals, and nutrients both directly by releasing glacier-trap resources and indirectly by exposing terrestrial landscape prone to runoff to fjord ecosystems 32,33 . (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies from the Godthaabsfjord have shown that sub‐glacial discharge of meltwater from marine terminating glaciers results in nutrient transport up into the photic zone, producing secondary blooms in late summer (Arendt et al ; Juul‐Pedersen et al ). This indicates that the amount of fresh water and how it is delivered to the fjord (surface or sub‐surface) may influence fjord circulation nutrient availability and subsequent productivity (Mortensen et al ; Lydersen et al ; Meire et al ).…”
mentioning
confidence: 99%